Sinus mucosa elevation using Bio-Oss® or Gingistat® collagen sponge: an experimental study in rabbits - Caneva, Marco; Lang, Niklaus P.; Garcia Rangel, Idelmo Junior [UNESP]; Ferreira, Sabrina [UNESP]; Caneva, Martina; De Santis, Enzo; Botticelli, Daniele [UNESP] (Wiley, 2017)
Objective: To describe the sequential healing in augmented sinus cavities with deproteinized bovine bone mineral (DBBM) granules or collagen sponges. Material and methods: Twenty albino New Zealand rabbits were included in the study. An incision was performed along the midline of the nasal dorsum, and the nasal bone was exposed. Circular bony windows with a diameter of 5 mm were prepared bilaterally. After elevation of the mucosa, the two sites were randomly filled with either DBBM or a collagen sponge. Five animals each were randomly sacrificed after 7, 14, 21 and 40 days, respectively. Results: At both sides, new bone was found forming from the resident pristine bone. During the first stage of healing, DBBM granules were surrounded by a denser connective tissue that was attached to the biomaterial surface and that was progressively mineralized. At the collagen sponge side, the biomaterial was almost completely resorbed and the space was reduced by to two-thirds already after 21 days. At both sides, after 40 days, mineralized bone and marrow spaces were occupying large areas of the elevated space. Conclusions: New bone was found forming from the pristine bony walls of the sinus and extending toward the most peripheral regions in both sites. While DBBM particles yielded osteoconductivity and were able to preserve over time the space within the elevated mucosa, the collagen sponge failed the goal of maintaining the space.
Keywords: animal study; collagen; deproteinized bovine bone mineral; sinus elevation